Silicon-carbon material, preparation method thereof and application thereof
By depositing silane gas, doping metal powder, carbon coating and acid treatment in porous carbon materials, preparing silicon carbon materials with improved volume expansion and electrochemical properties, solving the problem of insufficient cyclic stability and rate performance of existing silicon carbon materials in lithium-ion batteries, and achieving higher cyclic stability and rate performance.
Patent Information
- Application Number
- CN202411956824.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing silicon carbon materials in lithium-ion batteries have insufficient cycle stability and rate performance due to volume expansion problems, which limits their commercial applications.
Silicon carbon materials with improved volume expansion and electrochemical properties were prepared by depositing silane gas in the porous carbon material, doping metal powder, performing carbon coating and acid treatment.
It significantly improves the cycle stability and rate performance of silicon carbon materials, reduces the volume expansion rate, and ensures its long-term stability and cycle life as a negative electrode material for high-performance lithium-ion batteries.
Smart Images

Figure BDA0005216612530000091 
Figure BDA0005216612530000101 
Figure HDA0005216612600000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a silicon-carbon material, a preparation method thereof and applications thereof. Background Art
[0002] With the increasing scarcity of energy today, the development of secondary batteries with low expansion and high specific energy is urgent. In recent years, silicon has been considered to be a promising negative electrode material for high energy density lithium-ion batteries (LIBs) due to its high theoretical specific capacity (4200mAh g-1). However, compared with traditional commercial graphite negative electrodes, silicon faces large volume expansion (>300%) during lithium insertion / extraction, unstable solid electrolyte interface (SEI) and poor ion transport capacity, which hinders its commercial application.
[0003] Silicon-carbon composite materials can effectively improve the shortcomings of poor cycling stability of silicon, and the addition of carbon can also improve the conductivity of the material, thereby improving the rate performance of the material. The reserved pore structure can also alleviate the volume expansion of silicon itself. However, the effect of alleviating volume expansion is still insufficient, so there is an urgent need for a preparation method that can significantly reduce the volume expansion of silicon-carbon materials to ensure its long-term stability and cycle life as a high-performance lithium-ion battery negative electrode material. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the fact that the effect of silicon-carbon materials in alleviating volume expansion in the prior art is still insufficient, and to provide a method for preparing silicon-carbon materials. When the prepared silicon-carbon materials are used as negative electrode materials for batteries, they have good cycle stability and rate performance.
[0005] The present invention provides a method for preparing a silicon-carbon material, which comprises the following steps:
[0006] Step S1. In the presence of silane gas, a porous carbon material is deposited to obtain a porous silane carbon material;
[0007] Step S2. doping metal powder into the pores of the porous silane carbon material to obtain a metal-doped silicon-carbon composite;
[0008] The metal powder is selected from one or more of bismuth powder, tin powder, magnesium powder and aluminum powder;
[0009] Step S3. In the presence of a carbon source gas, carbon-coating the metal-doped silicon-carbon composite to obtain a carbon-coated metal-doped silicon-carbon composite;
[0010] Step S4: treating the carbon-coated metal-doped silicon-carbon composite with acid to obtain the silicon-carbon material.
[0011] In step S1, the operations and conditions of the deposition process may be conventional operations and conditions in the art.
[0012] In one embodiment, in step S1, the deposition temperature is 400°C to 700°C, for example, 560°C.
[0013] In one embodiment, in step S1, the deposition time is 3 to 9 hours, preferably 4 to 8 hours; for example, 6 hours.
[0014] In one embodiment, in step S1, the silane gas is heated to the deposition temperature at a heating rate of 2-8°C / min, for example, at a heating rate of 5°C / min.
[0015] In one embodiment, in step S1, the silane gas flow rate is 5 to 15 L / min, for example, 10 L / min.
[0016] In one embodiment, in step S1, the porous carbon is phenolic resin, activated carbon fiber, mesoporous carbon, asphalt, carbon nanotubes, coconut shell carbonized material or graphene; for example, coconut shell carbonized material.
[0017] In one embodiment, in step S1, the specific surface area of the porous carbon is 1600 to 2000 m 2 / g, for example 1832m 2 / g.
[0018] In one embodiment, in step S1, the pore volume of the porous carbon is 0.9 to 1.2 cm 3 / g, for example 0.9cm 3 / g.
[0019] In one embodiment, in step S1, the average pore size of the porous carbon is 1.60-1.85 nm, for example, 1.72 nm.
[0020] In step S1, the deposition equipment is conventional deposition equipment in the art, such as a fluidized bed.
[0021] In step S2, the doping operation and conditions may be conventional operations and conditions in the art.
[0022] In one embodiment, in step S2, the metal powder is tin powder or magnesium powder.
[0023] In one embodiment, in step S2, the average particle size of the metal powder is 1 to 3 um, for example, 2 um.
[0024] In a certain embodiment, in step S2, during the doping, the mass ratio of the metal powder to the porous silane carbon material is 1:(6-12), for example, 1:8.
[0025] In step S2, during the doping, the equipment used is conventional equipment in the art, such as a ball mill; the rotation speed of the ball mill is preferably 300 to 700 r / min, such as 500 r / min.
[0026] In step S3, the carbon coating operation and conditions may be conventional operations and conditions in the art.
[0027] In step S3, the carbon coating equipment is a conventional CVD equipment (vapor deposition equipment) in the art, such as a chemical vapor deposition furnace.
[0028] In one embodiment, in step S3, the temperature of the carbon coating is 400-600°C, for example, 500°C.
[0029] In one embodiment, in step S3, the carbon coating time is 6 to 12 hours, for example, 5 hours.
[0030] In one embodiment, in step S3, before carbon coating, the temperature of the carbon coating is heated to the carbon coating temperature at a heating rate of 2 to 8°C / min; the heating rate is preferably 2°C / min, 3°C / min, 4°C / min or 5°C / min; for example, 5°C / min; the inert gas is preferably argon.
[0031] In one embodiment, in step S3, the carbon source gas is selected from one or more of ethylene, acetylene, methane and propane; for example, a mixed gas of methane and acetylene;
[0032] Preferably, in the mixed gas of methane and acetylene, the volume ratio of methane to acetylene is 1:(0.4-4), more preferably, the volume ratio of methane to acetylene is 1:2, 1:3, 2:1, 2:3 or 3:2; for example, 1:2.
[0033] In step S4, the operation and conditions of the acid treatment may be conventional operations and conditions in the art.
[0034] In one embodiment, in step S4, the acid is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, such as hydrochloric acid.
[0035] In one embodiment, in step S4, the concentration of the acid is 8 to 16 mol / L; preferably 10 to 14 mol / L, for example 12 mol / L.
[0036] In one embodiment, in step S4, the acid treatment time is 1 to 50 hours, preferably 2 to 35 hours; for example, 2 hours, 10 hours or 30 hours.
[0037] In one embodiment, in step S4, the acid treatment time is preferably 6 to 35 hours, such as 8 to 16 hours; for example, 10 hours.
[0038] In one embodiment, in step S4, after the acid treatment, washing and drying are further included.
[0039] Preferably, the solution used for washing is a mixed solution of water and an alcohol solvent; the alcohol solvent is preferably ethanol;
[0040] Preferably, the drying temperature is 50-80°C, for example 60°C.
[0041] The present invention provides a silicon-carbon material, which is prepared by the silicon-carbon material preparation method as described above.
[0042] In one embodiment, the silicon-carbon material comprises a porous carbon substrate, silicon and a carbon coating layer; wherein the silicon is distributed in the pores of the porous carbon substrate, and the carbon coating layer is wrapped around the outer surface of the porous carbon substrate.
[0043] Preferably, the D50 (median diameter) of the silicon-carbon material is 2 to 18 μm, and more preferably 6 to 10 μm.
[0044] Preferably, the carbon content in the silicon-carbon material is 40wt% to 48wt%, for example, 42.8wt%, 45.6wt% or 46.1wt%.
[0045] Preferably, the silicon content in the silicon-carbon material is 40wt% to 50wt%, for example 48.8wt%, 49.2wt% or 49.3wt%.
[0046] Preferably, the specific surface area of the silicon-carbon material is 3 to 10 m 2 / g, for example 5.6m 2 / g, 6.3m 2 / g or 7.0m 2 / g.
[0047] Preferably, the tap density of the silicon-carbon material is 0.8 to 1.5 g / cm 3 , for example 1.09 g / cm 3 , 1.10g / cm 3 or 1.11 g / cm 3 .
[0048] The present invention also provides an application of the silicon-carbon material as described above in a battery.
[0049] In one embodiment, the silicon-carbon material is used to prepare the negative electrode plate of the battery.
[0050] In one embodiment, the battery is a lithium-ion battery.
[0051] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0052] The reagents and raw materials used in the present invention are commercially available.
[0053] The positive and progressive effects of the present invention are:
[0054] (1) The silicon-carbon material prepared by the present invention has a granular structure and a uniform size distribution, with a D50 of about 6-10 μm.
[0055] (2) When the prepared silicon-carbon material is used for the negative electrode in a lithium-ion battery, the full-charge expansion rate is low and the powder resistivity is small, which greatly improves the cycle stability and rate performance of the material and improves the charge dynamics and charge conductivity of the silicon-carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a flow chart for preparing the silicon-carbon material prepared in Example 1.
[0057] Figure 2 This is the SEM image of the silicon-carbon material prepared in Example 1. DETAILED DESCRIPTION
[0058] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0059] Example 1
[0060] Step S1
[0061] The porous carbon (commercially available; manufacturer: Shanghai Hanyan Activated Carbon Material Co., Ltd.; model: coconut shell carbonized material; BET specific surface area 1832m 2 / g, pore volume 0.9cm 3 / g, average pore size 1.72nm) was transferred to a fluidized bed device, and silane gas was introduced into the fluidized bed under the working state of the fluidized bed. The temperature was raised to 560°C at a heating rate of 5°C / min, the constant temperature time was 6h, and the silane gas flow rate was 10L / min. The porous carbon was floated by the airflow of the fluidized bed to make it in a suspended state, and the deposition of nano-silicon on the porous carbon material was achieved to obtain a porous silane carbon material.
[0062] Step S2
[0063] Then, 1.0 g of metal tin powder (commercially available; manufacturer: Beijing Xingrongyuan Technology Co., Ltd., average particle size 2 um) and 8.0 g of porous silane carbon material were placed in a ball mill and ball-milled for 5 hours at a rotation speed of 500 rpm to allow the metal tin powder to be doped into the pores of the porous silane carbon material as much as possible to obtain a porous metal-doped silicon-carbon composite material.
[0064] Step S3
[0065] The obtained porous metal-doped silicon-carbon composite material is transferred to a chemical vapor deposition furnace, and the temperature is raised to 500°C (heating rate is 5°C / min) under an argon inert atmosphere, and methane and acetylene are introduced as carbon source gases (methane: acetylene = 1:2). The CVD process is maintained at a constant temperature for 5 hours, and finally a carbon-coated porous metal-doped silicon-carbon composite is obtained, which appears as a black powder.
[0066] Step S4
[0067] The carbon-coated porous metal-doped silicon-carbon composite was treated in 12 mol / L HCl for 10 h, then washed thoroughly with pure water and ethanol, and finally dried under vacuum at 60°C, and the final product was collected to obtain a silicon-carbon material. (See the preparation flow chart of silicon-carbon materials Figure 1 )
[0068] Example 2
[0069] Step S1
[0070] The porous carbon (commercially available; manufacturer: Shanghai Hanyan Activated Carbon Material Co., Ltd.; model: coconut shell carbonized material; BET specific surface area 1832m 2 / g, pore volume 0.9cm 3 / g, average pore size 1.72nm) was transferred to a fluidized bed device. Under the working state of the fluidized bed, silane gas was introduced into the fluidized bed and the temperature was raised to 560°C at a heating rate of 5°C / min. The constant temperature time was 6h and the silane flow rate was 10L / min. The porous carbon was floated by the airflow of the fluidized bed to make it in a suspended state, and the deposition of nano-silicon on the porous carbon material was achieved to obtain a porous silane carbon material.
[0071] Step S2
[0072] Then, 1.0 g of metal tin powder (commercially available; manufacturer: Beijing Xingrongyuan Technology Co., Ltd., average particle size 2 um) and 8.0 g of porous silane carbon material were placed in a ball mill and ball-milled for 5 hours at a rotation speed of 500 rpm to allow the metal tin powder to be doped into the pores of the porous silane carbon material as much as possible to obtain a porous metal-doped silicon-carbon composite material.
[0073] Step S3
[0074] The obtained porous metal-doped silicon-carbon composite material is transferred to a chemical vapor deposition furnace, and the temperature is raised to 500°C (heating rate is 5°C / min) under an argon inert atmosphere, and methane and acetylene are introduced as carbon source gases (methane: acetylene = 1:2). The CVD process is maintained at a constant temperature for 5 hours, and finally a carbon-coated porous metal-doped silicon-carbon composite is obtained, which appears as a black powder.
[0075] Step S4
[0076] The carbon-coated porous metal-doped silicon-carbon composite was treated in 12 mol / L HCl for 2 h, then fully washed with pure water and ethanol, and finally dried in vacuo at 60° C., and the final product was collected to obtain a silicon-carbon material.
[0077] Example 3
[0078] Step S1
[0079] The porous carbon (commercially available; manufacturer: Shanghai Hanyan Activated Carbon Material Co., Ltd.; model: coconut shell carbonized material; BET specific surface area 1832m 2 / g, pore volume 0.9cm 3 / g, average pore size 1.72nm) was transferred to a fluidized bed device. Under the working state of the fluidized bed, silane gas was introduced into the fluidized bed and the temperature was raised to 560°C at a heating rate of 5°C / min. The constant temperature time was 6h and the silane flow rate was 10L / min. The porous carbon was floated by the airflow of the fluidized bed to make it in a suspended state, and the deposition of nano-silicon on the porous carbon material was achieved to obtain a porous silane carbon material.
[0080] Step S2
[0081] Then, 1.0 g of metal tin powder (commercially available; manufacturer: Beijing Xingrongyuan Technology Co., Ltd., average particle size 2 um) and 8.0 g of porous silane carbon material were placed in a ball mill and ball-milled for 5 hours at a rotation speed of 500 rpm to allow the metal tin powder to be doped into the pores of the porous silane carbon material as much as possible to obtain a porous metal-doped silicon-carbon composite material.
[0082] Step S3
[0083] The obtained porous metal-doped silicon-carbon composite material is transferred to a chemical vapor deposition furnace, and the temperature is raised to 500°C (heating rate is 5°C / min) under an argon inert atmosphere, and methane and acetylene are introduced as carbon source gases (methane: acetylene = 1:2). The CVD process is maintained at a constant temperature for 5 hours, and finally a carbon-coated porous metal-doped silicon-carbon composite is obtained, which appears as a black powder.
[0084] Step S4
[0085] The carbon-coated porous metal-doped silicon-carbon composite was treated in 12 mol / L HCl for 30 h, then fully washed with pure water and ethanol, and finally dried in vacuum at 60° C., and the final product was collected to obtain a silicon-carbon material.
[0086] Comparative Example 1
[0087] The preparation method is basically the same as that of Example 1, except that the method of treating with 12 mol / L HCl for 12 h is not used in Comparative Example 1.
[0088] Comparative Example 2
[0089] The preparation method is basically the same as that of Example 1, except that in Comparative Example 2, no metallic tin is added and the treatment with 12 mol / L HCl for 12 h is not used.
[0090] Experimental results and conclusions:
[0091] (1) Morphology test:
[0092] The silicon-carbon material obtained in Example 1 was subjected to a scanning electron microscope (SEM) test (eg Figure 2 ). Figure 2 It can be seen that the composite material presents a granular structure, and the particle size distribution is uniform and reasonable, and the particle size (D50) is about 6-10 μm.
[0093] (2) Specific surface area test method:
[0094] The NOVATOUCH BET tester from Quantachrome in the United States uses the GB / T19587-2017 gas adsorption BET method to determine the specific surface area of solid substances. The sample needs to be dried before use: 300°C for 2 hours, multi-point static BET method, nitrogen adsorption method, and adsorption medium nitrogen.
[0095] (3) Tap density test method:
[0096] American Quantachrome Autotap tap density tester, refer to GB / T38823-2020 silicon carbon;
[0097] The specific steps are as follows:
[0098] 1) Place the sample into the measuring cylinder of the tap density meter, vibrate, and rotate until the volume no longer decreases. Tap density = sample mass / volume after tapping;
[0099] 2) The volume of the measuring cylinder is 30 mL;
[0100] 3) Vibration frequency 250 times / min, amplitude 3mm, vibration 12h, load >30mL sample.
[0101] (4) Carbon content test method:
[0102] Carbon and sulfur analyzer, refer to GB / T38823-2020 silicon carbon;
[0103] (5) Silicon content test method:
[0104] Refer to GB / T38823-2020 silicon carbon, the specific steps are as follows: 1) The mass of the crucible is M0, the crucible is loaded with sample powder, the weight of the crucible is M1 (the sample powder is about 2.0g), the crucible tongs take the loaded crucible and put it into the heating chamber of the box furnace (muffle furnace), ensure that 5L / min compressed air is introduced, heat at 600℃ for 40min, then heat to 1000℃, keep the temperature for 5h, cool to room temperature, and then weigh the mass of the crucible m3;
[0105] 2) Silicon content = (M2-M0) / (M1-M0)×28.09 / 60.09×100%.
[0106] (6) Effect test:
[0107] The new silicon-carbon material, conductive carbon black (SP), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) prepared in the above Examples 1 to 3 and Comparative Examples 1 and 2 are uniformly mixed in a mass ratio of 95:1:2.5:1.5 to form a black slurry. The black slurry is coated on an 8μm copper foil, and then the pole piece is evenly coated and dried (the temperature is set to 60°C and the time is set to 12h) to obtain the negative pole piece. The electrolyte uses a LiPF6 solution, in which the concentration of LiPF6 is 1 mol / L, and the solvent used is a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a weight ratio of 1:1. Metal lithium is used as the counter electrode, and the diaphragm is a Cellgard2400 diaphragm, and the button battery is assembled in a glove box.
[0108] Full charge expansion test: for the negative electrode sheet of the button battery after rolling, test its thickness D1, then dissect its negative electrode sheet when the button battery is fully charged to 100% SOC, test its thickness D2, and then calculate the full charge expansion rate = (D2-D1) / D1*100%.
[0109] Powder resistivity test: The powder resistivity is tested using the four-probe method.
[0110] Cycle performance test: The battery cycle performance was tested at a charge and discharge rate of 1C / 1C, a voltage range of 2.5V-4.2V, and a temperature of 25±3℃ for 100 cycles.
[0111] Rate test: The constant current ratio is calculated as follows: constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity), where the cut-off voltage is 4.2 V. The test data are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115] As can be seen from Table 1, compared with Examples 1 to 3 and Comparative Example 2, when the material prepared by the preparation method of the present invention is used for the negative electrode sheet in a lithium-ion battery, the full-charge expansion rate and powder resistivity are low, that is, the full-charge expansion rate is ≤120.6%, and the powder resistivity is ≤5.89%, and it has high cycle stability and rate performance. In Comparative Example 1, adding metal tin but not using acid treatment shows poor cycle stability. After doping with metal tin, the volume expansion is further enhanced, which leads to a significant increase in the powder resistivity, a high overall expansion rate of the material, and a decrease in the rate performance.
Claims
1. A method for preparing a silicon-carbon material, characterized in that: It includes the following steps: Step S1. In the presence of silane gas, a porous carbon material is deposited to obtain a porous silane carbon material; Step S2. doping metal powder into the pores of the porous silane carbon material to obtain a metal-doped silicon-carbon composite; The metal powder is selected from one or more of bismuth powder, tin powder, magnesium powder and aluminum powder; Step S3. In the presence of a carbon source gas, carbon-coating the metal-doped silicon-carbon composite to obtain a carbon-coated metal-doped silicon-carbon composite; Step S4: treating the carbon-coated metal-doped silicon-carbon composite with acid to obtain the silicon-carbon material.
2. The preparation method according to claim 1, characterized in that It meets one or more of the following conditions: (1) In step S1, the deposition temperature is 400° C. to 700° C.; (2) In step S1, the deposition time is 3 to 9 hours; (3) In step S1, the silane gas is heated to the deposition temperature at a heating rate of 2 to 8°C / min; (4) In step S1, the silane gas flow rate is 5 to 15 L / min; (5) In step S1, the porous carbon is phenolic resin, activated carbon fiber, mesoporous carbon, asphalt, carbon nanotubes, coconut shell carbonized material or graphene; (6) In step S1, the specific surface area of the porous carbon is 1600 to 2000 m 2 / g; (7) In step S1, the pore volume of the porous carbon is 0.9 to 1.2 cm 3 / g; (8) In step S1, the average pore size of the porous carbon is 1.6 to 1.85 nm; (9) In step S1, the deposition equipment is a fluidized bed; (10) In step S2, the metal powder is tin powder or magnesium powder; (11) In step S2, the average particle size of the metal powder is 1 to 3 μm; (12) In step S2, during the doping, the mass ratio of the metal powder to the porous silane carbon material is 1:(6-12); (13) In step S2, the doping is performed using a ball mill; (14) In step S3, the carbon coating equipment is a chemical vapor deposition furnace; (15) In step S3, the carbon coating temperature is 400-600°C; (16) In step S3, the carbon coating time is 6 to 12 hours; (17) In step S3, before the carbon coating, the inert gas is heated to the carbon coating temperature at a heating rate of 2 to 8°C / min; (18) In step S3, the carbon source gas is selected from one or more of ethylene, acetylene, methane and propane; (19) In step S4, the acid is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid; (20) In step S4, the concentration of the acid is 8 to 16 mol / L; (21) In step S4, the acid treatment time is 1 to 50 hours; (22) In step S4, after the acid treatment, washing and drying are also included.
3. The preparation method according to claim 2, characterized in that: It meets one or more of the following conditions: (1) In step S1, the deposition temperature is 560° C. (2) In step S1, the deposition time is 4 to 8 hours; (3) In step S1, the silane gas is heated to the deposition temperature at a heating rate of 5°C / min; (4) In step S1, the silane gas flow rate is 10 L / min; (5) In step S1, the porous carbon is coconut shell carbonized material; (6) In step S1, the specific surface area of the porous carbon is 1832 m 2 / g; (7) In step S1, the pore volume of the porous carbon is 0.9 cm 3 / g; (8) In step S1, the average pore size of the porous carbon is 1.72 nm; (9) In step S2, the average particle size of the metal powder is 2 μm; (10) In step S2, during the doping, the mass ratio of the metal to the porous silane carbon material is 1:8; (11) In step S2, the rotation speed of the ball mill is 300 to 700 r / min; (12) In step S3, the carbon coating temperature is 500° C. (13) In step S3, the carbon coating time is 5 hours; (14) In step S3, before the carbon coating, the inert gas is heated to the carbon coating temperature at a heating rate of 2°C / min, 3°C / min, 4°C / min or 5°C / min; (15) In step S3, the inert gas is argon; (16) In step S3, the carbon source gas is a mixed gas of methane and acetylene; (17) In step S4, the acid is hydrochloric acid; (18) In step S4, the concentration of the acid is 10 to 14 mol / L; (19) In step S4, the acid treatment time is 2 to 35 hours; (20) In step S4, the solution used for washing is a mixed solution of water and an alcohol solvent; (21) In step S4, the drying temperature is 50 to 80°C.
4. The preparation method according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In step S1, the deposition time is 6 hours; (2) In step S2, the rotation speed of the ball mill is 500 r / min; (3) In step S3, before the carbon coating, the inert gas is heated to the carbon coating temperature at a heating rate of 5°C / min; (4) In step S3, in the mixed gas of methane and acetylene, the volume ratio of methane to acetylene is 1:(0.4-4), preferably, the volume ratio of methane to acetylene is 1:2, 1:3, 2:1, 2:3 or 3:2; for example, 1:2; (5) In step S4, the concentration of the acid is 12 mol / L; (6) In step S4, the acid treatment time is 2 h, 10 h or 30 h; (7) In step S4, the alcohol solvent is ethanol; (8) In step S4, the drying temperature is 60°C.
5. A silicon-carbon material, prepared by the preparation method according to any one of claims 1 to 4.
6. The silicon-carbon material according to claim 5, characterized in that: The silicon-carbon material comprises a porous carbon substrate, silicon and a carbon coating layer; wherein the silicon is distributed in the pores of the porous carbon substrate, and the carbon coating layer is wrapped around the outer surface of the porous carbon substrate.
7. The silicon-carbon material according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The D50 of the silicon-carbon material is 2 to 18 μm; (2) The carbon content of the silicon-carbon material is 40wt% to 48wt%; (3) The silicon content in the silicon-carbon material is 40wt% to 50wt%; (4) The specific surface area of the silicon-carbon material is 3 to 10 m 2 / g; (5) The tap density of the silicon-carbon material is 0.8 to 1.5 g / cm 3 .
8. The silicon-carbon material according to claim 7, characterized in that: It meets one or more of the following conditions: (1) The D50 of the silicon-carbon material is 6 to 10 μm; (2) The carbon content of the silicon-carbon material is 42.8wt%, 45.6wt% or 46.1wt%; (3) The silicon content in the silicon-carbon material is 48.8wt%, 49.2wt% or 49.3wt%; (4) The specific surface area of the silicon-carbon material is 5.6 m 2 / g, 6.3m 2 / g or 7.0m 2 / g; (5) The tap density of the silicon-carbon material is 1.09 g / cm 3 , 1.10g / cm 3 or 1.11 g / cm 3 .
9. Use of the silicon-carbon material according to any one of claims 5 to 8 in a battery.
10. The use according to claim 9, characterized in that It meets one or both of the following conditions: (1) The silicon-carbon material is used to prepare the negative electrode of the battery; (2) The battery is a lithium-ion battery.
Citation Information
Cited By
Silicon-carbon-based composite material, preparation method and application of silicon-carbon-based composite material in lithium ion battery
CN120072918A
Metal-doped biomass carbon negative electrode material and preparation method thereof
CN121439786A